Evaluating nutritional yield patterns through diverse cropping systems to enhance nutritional security in the eastern IGP of India - Choudhary, K.M.; Kalvania, K.C.; Ali, Shahid; Sinha, Pooja; Kumar, Sanjeev; Jat, R.K.; Bijarniya, Deepak; Krupnik, Timothy J.; Gathala, Mahesh K. (TAFSSA, 2024)
In rural communities of eastern Indo Gangetic Plains (EIGP), having a restricted range of food choices presents major obstacles to maintaining nutritional health and overall well-being. Numerous families mainly depend on basic crops like wheat and rice, resulting in a repetitive diet that is deficient in vital vitamins, minerals, and proteins. As a result, communities, especially women and children, often experience malnutrition and deficiencies in like iron and vitamins. Preschool children's severe acute malnutrition has increased from 6.6% to 7.7%, which is putting them at high risk of the children (National Family Health Survey-3). To address these complex changes, the on-farm research was set up by the Transforming Agrifood Systems in South Asia (TAFSSA) Initiative under CIMMYT with the partnership of CGIAR Institutes, JEEVIKA, and the Department of Agriculture in Nalanda district of Bihar, India, enhancing the nutritional diversity through cultivating diversified cropping systems.